CHEMO-IMMUNOLOGICAL STUDIES ON CONJUGATED CARBOHYDRATE-PROTEINS : VI. THE SYNTHESIS OFp-AMINOPHENOLα-GLUCOSIDE AND ITS COUPLING WITH PROTEIN - Goebel, Walther F. (The Rockefeller University Press, 1932)
1. The synthesis of p-aminophenol α-glucoside has been described. This glucoside can be coupled to any protein to yield a synthetic α-glucoside-protein complex. 2. A synthetic β-glucoside-protein complex has also been prepared. 3. These synthetic sugar-protein complexes have been used as immunizing antigens in order to ascertain whether α- and β-glucosidic unions influence the specificity of the immune response in animals. The results of the immunological studies are presented in the following paper.